Polish Anthropological Terminology in Słownik terminologii lekarskiej polskiej from 1881 - Jankowiak, Lucyna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
The aim of the article is to preliminarily analyse the Polish anthropological terminology included in the most important 19th-century Kraków Słownik terminologii lekarskiej polskiej [Dictionary of Polish Medical Terminology] by S. Janikowski, J. Oettinger and A. Kremer, which was created during the period when anthropology was emerging as a new science. Anthropological terms had appeared in Kraków’s medical dictionaries before (over 40%), but it was in S 1881 that they were first distinguished from medical terminology and marked with the qualifier antr. The anthropological terminology for S 1881 was prepared by prominent anthropologists who were also physicians: I. Kopernicki and J. Majer. Out of 195 Polish terms, over 70% apply to craniology and craniometry, reflecting the main direction of the development in Polish anthropology. The Polish terms are definitely indigenous. More than 80% are one- (55.4%) and two-element terms (26.2%). Synonymy is present in the analysed terminology (40.4%), although there is a visible tendency to limit the number of Polish terms in synonymic series to two (73.7%).